2018
DOI: 10.1021/jacs.8b00944
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Driven Bromide Oxidation and Ligand Substitution Photochemistry of a Ru Diimine Complex

Abstract: The complex [Ru(deeb)(bpz)] (RuBPZ, deeb = 4,4'-diethylester-2,2'-bipyridine, bpz = 2,2'-bipyrazine) forms a single ion pair with bromide, [RuBPZ, Br], with K = 8400 ± 200 M in acetone. The RuBPZ displayed photoluminescence (PL) at room temperature with a lifetime of 1.75 μs. The addition of bromide to a RuBPZ acetone solution led to significant PL quenching and Stern-Volmer plots showed upward curvature. Time-resolved PL measurements identified two excited state quenching pathways, static and dynamic, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…211 1 H NMR titrations indicated that the ion-paired bromide was preferentially located next to the ruthenium center. 210 Indeed, resonances associated with 5-H atoms of the 2,2′-bipyrazine ligand and 6-H atoms of the deeb ligand shifted to a larger extent (0.09 and 0.12 ppm, respectively) compared to very small shifts of the 3,3′-H atoms of the 2,2′-bipyrazine ligand. Moving from acetone to CH 2 Cl 2 drastically influenced the ground-and excited-state chemistry.…”
Section: Chemical Reviewsmentioning
confidence: 90%
See 3 more Smart Citations
“…211 1 H NMR titrations indicated that the ion-paired bromide was preferentially located next to the ruthenium center. 210 Indeed, resonances associated with 5-H atoms of the 2,2′-bipyrazine ligand and 6-H atoms of the deeb ligand shifted to a larger extent (0.09 and 0.12 ppm, respectively) compared to very small shifts of the 3,3′-H atoms of the 2,2′-bipyrazine ligand. Moving from acetone to CH 2 Cl 2 drastically influenced the ground-and excited-state chemistry.…”
Section: Chemical Reviewsmentioning
confidence: 90%
“…The bromine atom subsequently reacted with Br – to generate Br 2 •– with a rate constant of 1.1 × 10 10 M –1 s –1 . The formal one-electron reduction potential of bromine in acetone was estimated as E °(Br •/– ) = 1.44 ± 0.02 V vs NHE using Marcus theory. , Prolonged irradiation led to the formation of both the cis and trans isomers of [Ru­(bpz)­(deeb)­Br 2 ] that were isolated by column chromatography …”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
See 2 more Smart Citations
“…These methodologies generally involve the formation of charged species. Here, ion pairing plays an important role in solution, as indicated in recent publications [1][2][3][4]. The important role of ion pairing extends in fields like catalysis [5], organic synthesis [6][7][8], and the chemistry of flavonoids [9,10] and radical-induced DNA-strand breaks [11].…”
Section: Introductionmentioning
confidence: 96%